Analisis Peningkatan Kemampuan Kognitif Murid Pada Fase E Elemen Pemrograman Terstruktur Setelah Menggunakan Lms Mindlab - Rino Raihan Gumilang; Rizky Basatha (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Students' cognitive abilities in the Structured Programming element at the vocational secondary school level remain a challenge in the implementation of Phase E of the Merdeka Curriculum, particularly in the mastery of programming logic and problem-solving concepts. This study aims to analyze the improvement of cognitive abilities among Class X RPL students at SMK Antartika 2 Sidoarjo following the use of a website-based LMS entitled Mindlab, integrated with the Problem Based Learning (PBL) instructional model. The study employed a Time Series Design conducted across three meetings in May 2026. Cognitive ability data were collected through pre-test (O1, O2) and post-test (O3) instruments that had been validated by subject matter experts. The media validation yielded 83.14% (Very Valid), the learning module 85.59% (Very Valid), the subject matter 82% (Valid), and the cognitive test items 80.63% (Very Valid). Inferential analysis using the Paired Sample T-Test revealed a calculated t-value of 68.45 with 30 degrees of freedom (df) and a p-value of less than 0.001, indicating a statistically significant increase in students' cognitive abilities. The magnitude of cognitive improvement was further assessed using the Normalized Gain (N-Gain) test, which produced a mean score of 0.732, classified within the high gain category. User experience evaluation using the UEQ instrument showed that the majority of scales were positioned Above Average against the global benchmark. These findings indicate that LMS Mindlab is significantly and effectively capable of enhancing students' cognitive abilities in the Structured Programming element of Phase E.